Aromatic Plants as Efficient Intercrops Under Poplars (Populus deltoides) Bartram Ex Marshall) - Singh, Kamla; Singh, Virendra; Hussain, A.; Kothari, S.K. (Indian Forester, 1990)
Studies on agro-forestry based on poplar plantation coupled with non-conventional crops like aromaric plants (Mentha spp and Cymbopogon spp) for three years revealed no adverse effect of companion aromatic plants on poplar growth measured in terms of height and diameter. Further, while the herb and oil yield of Mentha spp decreased as compared to their sole cropping in second and third year, that of Cymbupogon spp remained equally economical in all the three years of this study. Thus, the aromatic grasses particularly Java Citronella, Palmarosa and Lemon grass were proved to be the efficient companion crops under poplar based agro-forestry.